Infantile spasms: Etiology, lead time and treatment response in a resource limited setting - Priyanka Surana; Joseph D. Symonds; Prabhar Srivastava; Thenral S. Geetha; Romit Jain; Ramprasad Vedant; Sakthivel Murugan; Subathra Mahalingam; Vivek Bhargava; Pradeep Goyal; Sameer M. Zuberi; Vivek Jain (Epilepsy & Behavior Reports, 2020)
This study explores the etiology and lead time to treatment for infantile spasm (IS) patients and their effect on treatment responsiveness, in a limited resource setting. Patients with IS onset age ≤12 months’, seen over 3 years were recruited retrospectively. Clinical information, neuroimaging and genetic results retrieved. Patients categorized into three primary etiological groups: Structural (including Structural Genetic), Genetic, and Unknown. The effect of etiology and lead time from IS onset to initiating appropriate treatment on spasm resolution, evaluated. Total 113 patients were eligible. Mean IS onset age was 6.86(±4.25) months (M: F 3.3:1). Patients were grouped into: Structural 85, Genetic 11 and Unknown 17. Etiology was ascertained in 94/113 (83.1%) with neonatal hypoglycemic brain injury (NHBI) being the most common (40/113, 36%). A genetic etiology identified in 17 (including 6 Structural Genetic, of which five had Tuberous Sclerosis). Structural group was less likely to be treatment resistant (p = 0.013, OR 0.30 [0.12–0.76]). Median treatment lead time – 60 days. Longer lead time to treatment was significantly associated with resistant spasms (χ2 for trend = 10.0, p = 0.0015). NHBI was the commonest underlying cause of IS. There was significant time lag to initiating appropriate treatment, affecting treatment responsiveness.